2023
DOI: 10.3390/molecules28155687
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Efficacy of Fingermark Enhancement Using ToF-SIMS

Abstract: Time-of-flight secondary ion mass spectrometry (ToF-SIMS) has been shown to enhance fingermark recovery compared to standard processes used by police forces, but there is no data to show how generally applicable the improvement is. Additionally, ToF-SIMS can be run in either positive or negative ion mode (or both), and there is no data on which mode of operation is most effective at revealing fingerprints. This study aims to fill these gaps by using ToF-SIMS to image fingerprints deposited on two common exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A study conducted by Bailey's team demonstrated that TOF-SIMS imaging was able to enhance fingerprint ridge details further than the standard process in the majority of cases. 23 Simultaneously, it has been demonstrated that using TOF-SIMS after standard processes proved successful and provided a further enhancement, pushing TOF-SIMS towards operational deployment. 24 In addition, current research still faces challenges in developing handprints left on non-planar or large-sized objects, which creates difficulties in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Bailey's team demonstrated that TOF-SIMS imaging was able to enhance fingerprint ridge details further than the standard process in the majority of cases. 23 Simultaneously, it has been demonstrated that using TOF-SIMS after standard processes proved successful and provided a further enhancement, pushing TOF-SIMS towards operational deployment. 24 In addition, current research still faces challenges in developing handprints left on non-planar or large-sized objects, which creates difficulties in practical applications.…”
Section: Introductionmentioning
confidence: 99%